Association of serum PAPP‐A levels in first trimester with small for gestational age and adverse pregnancy outcomes: systematic review and meta‐analysis. (17th February 2017) - Morris, R. Katie; Bilagi, Ashwini; Devani, Pooja; Kilby, Mark D.
Abstract: Objectives: To determine association, and predictive ability, of first trimester maternal serum pregnancy associated plasma protein A (PAPP‐A) with adverse pregnancy outcomes. Method: Searches of Medline, Embase and CINAHL (inception September 2015) for studies including pregnant women with first trimester PAPP‐A and assessment of pregnancy outcomes. Study characteristics, quality and results extracted. Meta‐analysis of odds ratios (ORs), and likelihood ratios (LRs) and 95% confidence intervals (CI). Results: Thirty‐two studies including 175 240 pregnancies. PAPP‐A <5th centile had a moderate association with: birth weight <10th centile OR 2.08 (95% CI 1.89–2.29), <5th centile OR 2.83 (95% CI 2.52–3.18); pre‐eclampsia OR 1.94 (95% CI 1.63–2.30), preterm birth <37 weeks OR 2.09 (95% CI 1.87–2.33), and composite adverse outcome OR 3.31 (95% CI 1.80–5.11). The predictive ability was poor: Birth weight <10th centile LR + ve 1.96 (95% CI 1.58–2.43), LR‐ve 0.93 (95% CI 0.89–0.98); birth weight <5th centile LR + ve 2.65 (95% CI 2.35–2.99), LR‐ve 0.85 (95% CI 0.74–0.98); PTB <37 weeks LR + ve 1.84 (95% CI 1.41–2.39), LR‐ve 0.92 (95% CI 0.87–0.98). Conclusions: First trimester low maternal serum PAPP‐A is associated with adverse pregnancy outcome, but predictive values are poor. Further work should address PAPP‐A as a continuous variable in combination with other prognostic markers as a prediction model. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known on this topic? Low levels of PAPP‐A are associated with small for gestational age and pre‐eclampsia. What does this study add? Low maternal serum PAPP‐A in the first trimester has an association with adverse pregnancy outcome particularly if levels are very low (<1st centile). For an individual prediction is poor, thus, the majority of adverse outcomes will occur in the group without an abnormally low PAPP‐A. Future research is required to develop prediction models and effective interventions.